Lymphoscintigraphy in Lymphedema - Igor Iskra; Tatjana Bogović Crnčić; Neva Girotto (Acta Clinica Croatica)
Lymphedema is a chronic, progressive condition caused by impaired lymphatic transport, leading to edema in the lower and/or upper extremities, depending on the underlying cause. The diagnosis is based on clinical examination, ultrasound findings, and imaging tests. Treatment is mostly conservative, usually long-term, and often yielding unsatisfactory results. Recently, surgical options have also become available. Lymphoscintigraphy, a non-invasive and simple nuclear medicine imaging technique, is considered the method of choice in diagnostic workup. It consists of intracutaneous or subcutaneous application of colloidal particles labelled with radioactive technetium-99m and two-dimensional or three-dimensional gamma camera imaging. Lymphoscintigraphy helps differentiate lymphedema from edema of another origin, assess disease severity, and evaluate surgery outcome. However, the procedure is not fully standardized, especially in terms of semiquantitative methods, which are additionally used in disease staging; however, their implementation varies depending on local experience and expertise.